Competition Indexes to Evaluate Tree Growth in a Semi-Deciduous Seasonal Forest - Lustosa Junior, Ilvan Medeiros; Castro, Renato Vinícius Oliveira; Gaspar, Ricardo de Oliveira; Araújo, Juliana Baldan Costa Neves; Aquino, Fabiana de Gois (Floresta e ambiente, 2019)
ABSTRACT Most of the studies that analyze the behavior of tree competition approach even-aged plantations. Therefore, it is possible to notice a lack of this kind of information regarding natural forests with high biodiversity. The objective of this study was to evaluate the competition in a fragment of Semi-Deciduous Seasonal Forest, according to the ecologic group, light depending and non-depending groups for all species sampled in the fragment. The Distance Independent Competition Index and Semi-Distance Independent Competition Index were applied in this study. The basal area in larger trees index, without the radius of influence, was the most efficient to analyze how the competition affects the growth of the specimens in the studied fragment. It was stated that evaluating the competition per ecologic group is more efficient. The results confirm that the forest competition cannot be determined by considering only a fixed radius of influence that embraces the neighbors and the subject tree. RESUMO A maioria dos estudos que analisa o comportamento da competição arbórea é voltada para plantios homogêneos e equiâneos. Nota-se, portanto, uma carência de informações deste tipo em florestas naturais de elevada biodiversidade. Objetivou-se com este trabalho avaliar a competição em um fragmento de Floresta Estacional Semidecidual, por grupo ecológico, grupos demandantes e não demandantes de luz para todas as espécies amostradas no fragmento. Foram empregados índices de competição independentes da distância e semidependentes da distância. O índice BAL (basal area in larger trees), sem raio de influência, obteve o melhor desempenho para analisar como a competição afeta o crescimento dos indivíduos no fragmento estudado. Concluiu-se que avaliar a competição por grupo ecológico é mais eficaz, e os resultados confirmam que a competição florestal não pode ser determinada apenas pela aplicação de um raio fixo de influência dos vizinhos em relação à árvore-objeto.